1995
DOI: 10.1159/000282767
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Structure of Ureteral Muscularis to in vitro Spontaneous Contractions

Abstract: We investigated the anatomical structure of the smooth muscle layers of the mid portion of the canine ureter. In transverse sections the inner muscle bundles appear to be oriented longitudinally and the outer muscle bundles appear to be oriented in a circular configuration. In sections cut parallel with the longitudinal axis of the ureter, the inner and outer bundles appear to be oblique and are oriented in a mesh-line manner. In oblique sections, cut parallel with the helically oriented ureteral muscle, bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
5
2
1
Order By: Relevance
“…As EFS induces contraction through the release of various mediators from the tissue and carbachol stimulates contraction via muscarinic receptors, all four suspension methods are suitable for analysing ureteric responses to a variety of stimuli. These results are in contrast to a previous report by Morita et al [13] who, using canine ureter, showed that spiral segments were more responsive to noradrenaline than were longitudinal or ring segments. In addition, that report indicated that ring and longitudinal segments had very low levels of spontaneous contraction, caused by disruption of the muscular bundles, which is avoided using the spiral‐cut method.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As EFS induces contraction through the release of various mediators from the tissue and carbachol stimulates contraction via muscarinic receptors, all four suspension methods are suitable for analysing ureteric responses to a variety of stimuli. These results are in contrast to a previous report by Morita et al [13] who, using canine ureter, showed that spiral segments were more responsive to noradrenaline than were longitudinal or ring segments. In addition, that report indicated that ring and longitudinal segments had very low levels of spontaneous contraction, caused by disruption of the muscular bundles, which is avoided using the spiral‐cut method.…”
Section: Discussioncontrasting
confidence: 99%
“…The reports mentioned used human or sheep ureters to obtain spontaneous contractility. The present results indicate that swine ureters also show spontaneous contractility, in contrast to the work of Morita et al [13] with canine ureter. This may suggest that the swine ureter provides a better model for the study of ureteric physiology than the canine ureter.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…, Morita et al . ). Therefore, and as expected, the nature of muscle contractions and electrical activities are not the same among these structures.…”
mentioning
confidence: 97%